The Use of Digital Smart Boards as a Means of Supporting TPACK-Based Interactive Learning - Winayu, Isnaeni Machra (PPSDP International Journal of Education, 2024)
A new challenge in the world of education must be able to increase the attractiveness of learning by developing technology-based learning media with digital smart boards.   This study aims to observe learning devices and models that use Smart Board Digital as a TPACK-based learning tool on learning quality. A type of research that uses data in the form of numbers to analyze and produce empirically measurable information. In this data collection study, the researcher used observation, questionnaire, and documentation techniques.  The analysis techniques used are T-test and F-test. TPACK-based learning tools using Digital Smart Board have an effect on the quality of learning.  There is a significant influence between the development of a learning model using TPACK-based Digital Smart Board on the quality of learning at SMPIT Mutiara Cendekia Lubuklinggau. Interactive Whiteboard revolutionizes the classroom experience by allowing teachers to display a variety of multimedia content such as videos, images, and interactive simulations directly on a large touch-sensitive screen that highly motivates students to learn. An innovative media that is able to attract students’ attention to be actively involved in learning so that students’ grades in learning can be better.  One of them is the smart board learning media.